THE EFFECT OF THE MEDICAL AND PREVENTIVE TREATMENT MANAGEMENT ON THE PROGRESS OF MAJOR DENTAL DISEASES IN CHILDREN WITH DYSPLASTIC SCOLIOSIS - Korotych, N.M.; Dobroskok V.О.; Kolisnyk І.А.; Popelo, Yu.V.; Vashchenko І.Yu.; Ilik, R.R. (World of Medicine and Biology, 2018)
The clinical manifestations of the dental caries, fluorosis and gingivitis had been studied in children with dysplastic scoliosis Ι-ΙΙ degrees. The medical and preventive treatment management complex has been developed and tested in clinic, it has a aiming at preventing the occurrence and the subsequent progression of the main dental diseases in these children. The high clinical efficacy has been confirmed for this treatment complex. In one-year period the reduction of the increment of permanent teeth dental caries was 26.17% and 43.75% in 2-year period. The sustainable clinical remission of gingivitis was achieved, as evidenced by the reduction of the PMA index by 39.06% after 12 months. The use of the proposed management plan also had a significant prolonged medical-and-prophylactic effect on the hard tooth tissues with fluorosis.